Data structures and algorithms in Java - Goodrich, Michael T.; Tamassia, Roberto 1960-; Goldwasser, Michael H. 1969- (Singapore Wiley, 2015)
"The design and analysis of efficient data structures has long been recognized as a key component of the Computer Science curriculum. Goodrich, Tomassia and Goldwasser's approach to this classic topic is based on the object-oriented paradigm as the framework of choice for the design of data structures. For each ADT presented in the text, the authors provide an associated Java interface. Concrete data structures realizing the ADTs are provided as Java classes implementing the interfaces. The Java code implementing fundamental data structures in this book is organized in a single Java package, net.datastructures. This package forms a coherent library of data structures and algorithms in Java specifically designed for educational purposes in a way that is complimentary with the Java Collections Framework"--Publisher's website.
Java primer -- Object-oriented design -- Fundamental data structures -- Algorithm analysis -- Recursion -- Stacks, queues, and deques -- List and iterator ADTs -- Trees -- Priority queues -- Maps, hash tables, and skip lists -- Search trees -- Sorting and selection -- Text processing -- Graph algorithms -- Memory management and B-trees.
Kurt Espinosa (Recommending Faculty) : Sciences Cluster
Includes bibliographical references (pages 710-713) and index.
Keywords: Java (Computer program language); Data structures (Computer science); Computer algorithms